Biodecolorization of azo dye Acid Black 24 by Bacillus pseudomycoides: Process optimization using Box Behnken design model and toxicity assessment. (December 2019) - Kumar, Naveen; Sinha, Surbhi; Mehrotra, Tithi; Singh, Rachana; Tandon, Simran; Thakur, Indu Shekhar
Abstract: Bacterial strain Bacillus pseudomycoides, isolated from domestic wastewater was used to decolorize azo dye Acid Black 24. Response Surface Methodology based on Box- Behnken model was used to optimize the conditions for maximum dye decolorization. High regression coefficient values (adjusted R 2  = 0.9317 and predicted R 2  = 0.8343) confirmed that the predicted values are in compliance with the experimental values implying the appropriateness of the employed polynomial regression model. The adequacy of the model was validated by different descriptive statistics viz. lack of fit, adequate precision, F and p values. 96.79% of dye decolorization was achieved at pH 7, temperature 37 °C and 40 mg L −1 dye concentration. The activities of oxido-reductive enzymes like lignin peroxidase, laccase and azoreductase were found to be induced during the dye decolorization process. The biodegradation of the dye was assessed by HPLC, FTIR and UV spectroscopy. Genotoxicity and phytotoxicity studies substantiated the nontoxic nature of the degraded dye. Graphical abstract: Unlabelled Image Highlights: Biodecolorization and degradation of Acid Black 24 dye by bacterial strain Optimization of process parameters using RSM based Box-Behnken design model At optimized conditions, about 96% dye decolorization was achieved within 24 h. Biodegradation of dye was established by various analytical approaches. Degraded dye showed less genotoxic and phytotoxic effects.